Extension–torsion–inflation coupling in compressible electroelastomeric thin tubes. (March 2020) - Saxena, Shashank; Barreto, Darius Diogo; Kumar, Ajeet
We present an axisymmetric and axially homogeneous variational formulation to obtain coupled extension–torsion–inflation deformation in compressible electroelastomeric tubes in the presence of axial and radial electric fields. We show that such deformations occur under the following two conditions: (1) only the axial electric field is imposed, with the electric poling direction in the tube (if present) lying in the radial plane; and (2) only the radial electric field is imposed within the tube, with the electric poling direction (if present) also along the radial direction. The poling direction in condition (1) generates helical anisotropy in the tube. We then obtain the governing differential equations necessary to solve the above deformation problem for thick tubes. We further apply the thin tube limit to obtain simplified algebraic equations to solve the same deformation problem. The effect of applied electric field parameters on the extension–inflation coupling and induced internal pressure vs. imposed inflation behavior is finally presented through numerical solution of the above obtained algebraic equations. The study will be useful in designing soft electroelastic tubular actuators.